2020
DOI: 10.1186/s12978-020-0862-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to facilitate safe sexual practices in adolescents through integrated health systems in selected districts of Zimbabwe: a mixed method study protocol

Abstract: Background Zimbabwe has the highest teenage pregnancy rate in Sub Saharan Africa. Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) prevalence in adolescents that are from tribes that perform cultural initiations and subscribe to certain norms are higher than the national prevalence which is estimated at 12% (18 and 13.6% respectively) in Zimbabwe. Indigenous Health Systems (IHSs) and Modern Health Systems (MHSs) in Zimbabwe run parallel thereby introducing challenges in the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…In research there is need that findings of qualitative studies be put into context and be confirmed by other authors (Creswell, 2013,Nunu et al, 2020, Tobin and Begley, 2004. Though the findings of a qualitative study maybe unique, ideas could be applicable to other different study settings (Creswell, 2013,Nunu et al, 2020, Tobin and Begley, 2004. High levels of objectivity and honesty were observed in collecting, analysing and interpretation of the data.…”
Section: Conformability and Transferabilitymentioning
confidence: 95%
See 4 more Smart Citations
“…In research there is need that findings of qualitative studies be put into context and be confirmed by other authors (Creswell, 2013,Nunu et al, 2020, Tobin and Begley, 2004. Though the findings of a qualitative study maybe unique, ideas could be applicable to other different study settings (Creswell, 2013,Nunu et al, 2020, Tobin and Begley, 2004. High levels of objectivity and honesty were observed in collecting, analysing and interpretation of the data.…”
Section: Conformability and Transferabilitymentioning
confidence: 95%
“…This is a process that is implemented to ensure that the whole inquiry process yields robust and accurate findings (Nunu et al, 2020). The following were taken into consideration during the conceptualisation and implementation of the research inquiry:…”
Section: Trustworthinessmentioning
confidence: 99%
See 3 more Smart Citations